Mental health analysis and resilience psychological factors during pandemic among port health 0fficers: A study in Sabang, Indonesia - Friza, Maisarah; Syahrul, Syahrul; Mawarpury, Marty (Narra Sains Indonesia, 2024)
The coronavirus disease 2019 (COVID-19) pandemic has had a negative impact on the mental health of health workers worldwide. Many studies examined the mental health of the frontline health workers in hospitals, but similar research on health workers at the port entries has yet to be found. The aim of this study was to determine the mental health issue and its associated factors and to determine psychological resilience factors of port health workers in Sabang, Indonesia during the COVID-19 pandemic. A retrospective mixed method study was conducted among 38 port health officers. Total sampling included those working from January 2020 to March 2023. The information on age, gender, qualification, working time and working place of the respondents were collected and the mental health was assessed using the Depression Anxiety Stress Scale (DASS-21). The correlation and association between the socio-demographic data and mental health were tested with Spearman and chi-squared test, respectively. The qualitative study on psychological resilience factors were performed with interviews and analyzed with NVivo. This study indicated that 47.4% of port health officers experienced depression, 63.1% anxiety and 50.0% stress. Age and working time significantly affected the mental health. Age correlated positively and significantly with anxiety (p<0.0001) and stress (p<0.0001), while working time significantly affected the anxiety (p=0.003). The psychological resilience factors identified were spirituality, positive emotions, official support and personal wellbeing that helped the workers taking learned lessons. In conclusion, mental health issue is high among frontline workers during the pandemic highlighting the importance of the prevention measures to ensure the work performance among employee.